Ex vitro rooting of Drosophyllum lusitanicum micropropagated shoots improves acclimatization - Gonçalves, Sandra (2013)
High frequency survival of in vitro propagated shoots of Drosophyllum lusitanicum, an endangered insectivorous plant native of the southern part of the Iberian Peninsula and northern Morocco, through ex vitro rooting was accomplished. All the ex vitro rooting treatments performed in the present study favoured high acclimatization rates compared to that of in vitro rooting. It was observed that ex vitro rooting was strongly influenced by auxin type and concentration. Of the various treatments, ex vitro rooting after dipping the basal end of in vitro derived shoots in 1 g L-1 indole-3-butyric acid for 2 min facilitated the best rooting with a mean of 5 roots in 85% shoots and highest survival percentage. Rooted shoots exhibited lateral roots and presence of root hairs. Ex vitro rooting of D. lusitanicum favours rooting and hardening in a simple step with reduction of micropropagation cost.